Local Employment Multiplier: Evidence from Relocation of Public-Sector Entities in South Korea - Hwanoong Lee; Changsu Ko; Wookun Kim (Center for Economic Studies and ifo Institute (CESifo), 2023)
We exploit a series of public-sector entity relocations in South Korea as an exogenous source of variation in public sector employment to estimate the local employment multiplier. We find that the introduction of one public sector employment position increases private sector employment by one unit, primarily driven by the service sector. Consistent with existing literature, we document that the effect of public employment on private employment is highly localized. In addition to changes in private employment, we also discover that the relocations led to a positive net influx of residents into the treated neighborhoods; this effect is also localized. Lastly, by estimating the local employment multiplier for each relocation site, we document the heterogeneity of the local employment multiplier and provide suggestive evidence that this het-erogeneity is shaped by the local economic environment's capacity to accommodate additional general equilibrium responses.
Keywords: H31; J45; J61; R11; R23; R58; 330; employment multiplier; public employment; spatial spillover; migration; heterogeneity